Ocins database: a database of bug-busters from Bifidobacterium, Lactobacillus, and Enterococcus. Issue 4 (13th June 2019) - Choyam, Shilja; PSN, Suresh; Pandey, Rahul; Kammara, Rajagopal
Abstract : The ocins are antimicrobial polypeptides produced by probiotic microbes, such as Lactobacillus, Enterococcus, Streptococcus, Leuconostoc and Bifidobacterium . They are produced in response to stress and for the self-defense of the bacterium. It is indispensable to understand their mechanistic characteristics, structures, and functions, if the food industry is to reduce contamination levels and produce germfree foods. Databases of the ocins that are readily accessible to the food industry are scarce, but urgently required. Therefore, we established a very useful, unique, and a simple ocin database, which not merely provides information about ocins, but also directs their utilisation in the food industry. The database includes information about each ocin, its amino acid sequence, molecular weight, and isoelectric point. The database also possesses all the currently known ocin (probiotic origin only) sequences and structures, target organisms, and relevant to food industries (aqua culture, dairy and meat industries), which is hard to obtain in other databases. The database is free for public and accessed athttp://ocins.cftri.com/ocins/ .